Luiz Gonzaga, o sertão em movimento - Vieira, Maria Sulamita de Almeida (1999)
The mam objective of this thesis is to analyze the "sertão" representational aspects on Luiz Gonzaga's songs. The purpose here is to focus on his production that was broadcast between 1947 and 1957 - period of time during what he acquired a significant role in the Brazilian musical field. To understand the reasons of that phenomenon it was necessary to look at the way that both, the "baião" ( that it is seen here in its generic term) and the artistic role of its main interpreter were created as inseparable historic processes. Facing these arguments and having in mind the musician's great talent, it was examined a set of internal variables in the field to identify the relationship between the field and the wider social context. It is argued that culture is a dynamic process and the "baião" music is a significant part of the Brazilian culture - the "baião" is seen here as a differentiated language through which the "sertão" is created as a symbolic construct. As the songs always portray a multiplicity of representations (that evokes religious tradition, beliefs, feelings, habits, popular parties, etc.) one is specially emphasized - the representation related to migration issues. The constancy of very expressive images for cultural production is focused and analyzed. Luiz Gonzaga's songs have strong appeal to his roots and he generally relates the migrants departure to drought representations. Furthermore, his song addresses the listener through an ideal "sertão" imagery, that evokes a homesickness feeling. ln this sense, those departure imageries are always related to a migrant' s dream return, where memories and utopias walk together. These songs are seen here as dynamic language, and they put together different experiences and traditions. It is also argued that "baião" is bigger than "sertão" simple representation. Actually, it is a combination of different cultural elements from which new simbols and pictures are created. ln this sense, a cultural struggle occurs, which means some kind of refuse to stigmatization that happens through the evocation of work, bravery, pleasure and dignity imageries as opposed to a "sertão" represented by desolation, poverty and calamity. Luiz Gonzaga's songs play a significant function for the relationship between the migrant and the city. Doing so, the songs help the migrant to perceive new contexts and also to create a new concept about the Northeast of Brazil.